The effect of principal supervision and teacher work motivation on teacher job satisfaction - Maryanti, Rina Dwi; Arafat, Yasir; Eddy, Syaiful (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The article aimed to determine and analyze the effect of Principal Supervision, Teacher Work Motivation on Job Satisfaction of Public Elementary School Teachers at Plakat Tinggi District. This type of research was descriptive quantitative. The sample in the study was 140 respondents with data collection techniques in the form of a questionnaire (questionnaire). The results showed that: 1) there was a significant effect of principal supervision on teacher job satisfaction, 2) there was a significant effect of teacher work motivation on teacher job satisfaction, 3) there was a significant influence between principal supervision and teacher work motivation on job satisfaction teacher.